Gender representation in the puppet shows conducted by the children's section of the National library of the Philippines - Enarsao, Czarina Mae B. (2018)
This research sought to describe the gender representation as portrayed by the library puppet shows conducted by the National Library of the Philippines-Children's Section. As gender is performed in the library puppet shows through the puppeteers and the puppets themselves, several viewpoints were considered: from the peripheral observers, from the children's librarians, and from the audience. The researcher used three methods to obtain the necessary data needed, specifically, content analysis, interviews, and focus group discussions. Each character per puppet show was identified through an analysis of their character, behavior, and communication. The results of the research showed that there are disparities between the intent of the children's librarians and the perception of the audience on how gender was represented. Attributes like tone of the voice, color, and personalities, helped in identifying whether the character is oriented to male or female embodiment. The usage of animals as characters did not impede the recognition of underrepresented female characters and the detection of stereotypical images among males and females. Male characters were described as physically and verbally aggressive yet they were also observed as confident, energetic, enthusiastic, and committed at the same time. On the other hand, female characters played victim roles but they were given redemption and noteworthy qualities along the end of the stories. Descriptors: library puppet shows, gender representation, children's services, public library, content analysis